Development of an AI-powered exchange platform (I) - Chong, Zhe Ming (Nanyang Technological University, 2023)
This report details a final year project that involved helping a company develop a platform for trading cryptocurrencies. The platform is used by investors, who can use it to view and manage their portfolio as well as make investments. The report provides a summary of the project's purpose, goals, and details of the work carried out. Together with visuals that help clarify the project's needs, the report also provides information about the tools and resources used. There are also user interfaces that depict how the application will seem in use coupled with the functional requirements of the application. The report also discusses testing, and it concludes with a summary of the project and the author's thoughts on it. The report will only cover the tasks that the author participated in because this is a large project and different tasks were assigned to different team members.